Assessment of Physico-chemical Characteristics of Tomato (Solanum lycopersicum) Stored under Diffusion Channel System - Kandasamy, Palani (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted to extend the shelf-life of tomato by diffusion channel system at the Institute of Agriculture, Visva-Bharati University, Sriniketan, West Bengal during 2010–12. Diffusion channel length 60, 120, 180 and 240 mm and diameter 3, 6, 9 and 12 mm were tested. The storage chambers of two liters capacity made of polyethylene tetrachloride were used. Tomato samples of 800±20 g at breaker stage were taken in each chamber and stored at 10, 20 and 30 °C. Quality characteristics such as physiological loss in weight (PLW), visual quality index (VQI), firmness, total soluble solids (TSS), titratable acidity, total sugars, ascorbic acid, lycopene and colour change (ΔE) were tested before and after storage to distinguish the relative changes. The stored tomato attained market acceptability after 40, 32 and 23 days at 10, 20 and 30 °C respectively under diffusion channel system. Minimum PLW of 3.37–3.74%, highest VQI number of 6.9–7, maximum firmness of 90–94N, titratable acidity as high as 0.46–0.48%, ascorbic acid content as low as 22.97 mg 100 g-1, lycopene formation as low as 2.58–2.62 mg 100 g-1, minimum ΔE of 29.87, TSS of 5.32–5.87 °Brix and total sugar content of 3.31–3.71 g 100 g-1 were recorded in chambers with diffusion channel length 180 mm and diameter 9 mm at 10 and 20 °C. Firmness, acidity and ascorbic acid were found significant (p≤0.05) by temperature, channel length and diameter. Total sugars and lycopene content had a significant difference with temperature and channel diameter. Temperature had a significant effect on TSS but length and diameter of channel had no significant effect.